Low-temperature-resistant high-skid-resistance automobile cover tyre and preparation method thereof

Through the combination of specific formula rubber materials and modified fillers and modified resins, the problem of degradation of existing low-temperature anti-slip car tires at extremely low temperatures is solved, and excellent anti-slip, waterproof and mechanical stability in low-temperature environments are achieved .

CN119490700APending Publication Date: 2025-02-21SUNTOP TIRE WUXI CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411638900.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The existing low-temperature and anti-slip car tires have reduced grip and anti-slip performance at extremely low temperatures, and the nail tires cause wear on the road surface, making them not suitable for urban road use.

Method used

Rubber materials with specific formulations, including natural rubber, mixed rubber, plasticizer, anti-aging agent, vulcanizing agent, accelerator, dispersant, anti-slip agent, activator, modified filler and modified resin, through modified filler and modified resin The addition of the elastic resin forms a composite surface structure and modified particles, improving the anti-slip, waterproof and mechanical stability of the rubber system.

Benefits of technology

Maintain excellent anti-slip, waterproof and low-temperature resistance in low-temperature environments, while improving mechanical stability, suitable for extreme low-temperature and urban road conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005137901790000161
    Figure BDA0005137901790000161
  • Figure BDA0005137901790000171
    Figure BDA0005137901790000171
  • Figure BDA0005137901790000172
    Figure BDA0005137901790000172
Patent Text Reader

Abstract

The invention relates to the field of rubber tires, in particular to a low-temperature-resistant high-skid-resistance automobile cover tire and a preparation method thereof. The low-temperature-resistant high-skid-resistance automobile cover tire is prepared from the following raw materials in parts by mass: 40 to 50 parts of natural rubber, 20 to 40 parts of mixed rubber, 10 to 15 parts of plasticizer, 1 to 2.5 parts of anti-aging agent, 1 to 2 parts of vulcanizing agent, 1 to 2 parts of accelerant, 2 to 3 parts of dispersing agent, 3 to 8 parts of skid-resistant agent, 2 to 3 parts of activating agent, 30 to 50 parts of modified filler and 20 to 30 parts of modified resin. The rubber material prepared by the invention and the automobile cover tire prepared from the rubber material can keep excellent waterproof, anti-aging and mechanical stability performances in a low-temperature environment while ensuring excellent low-temperature resistance and anti-skid performance, and have very excellent market prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of rubber tires, and in particular to a low-temperature-resistant and highly anti-skid automobile outer tire and a preparation method thereof. Background Art

[0002] The car's outer tyre is a circular elastic connector between the car and the road. It is the car's running structure. It transmits the car's driving, traction, acceleration, steering and braking forces to the ground, such as driving force, traction, braking force and steering force. Secondly, the tire must enable the car to travel freely, operate stably and safely at high speeds in various climates, road surfaces and speeds. Finally, the tire must buffer vibrations, reduce noise and provide a comfortable ride.

[0003] In recent years, with the impact of global climate change, the frequency of extreme cold weather in winter has increased significantly, especially in the northern regions of my country such as Northeast China, Northwest China, and Inner Mongolia, where the winter temperature is often below -20℃ or even lower. Under such extreme low temperature conditions, the road surface is prone to snow and ice accumulation, leading to frequent traffic accidents. Therefore, it is particularly important to develop a car tire that can maintain excellent anti-skid performance in low temperature environments.

[0004] The low-temperature resistant and anti-skid car tires on the market mainly include the following types: Ordinary winter tires: These tires usually use a soft rubber formula to maintain softness at low temperatures. However, ordinary winter tires will still harden at extreme low temperatures, affecting their grip and anti-skid performance; Spiked tires: Spiked tires have metal spikes embedded in the tread to improve grip on icy and snowy roads. Although spiked tires perform well on icy and snowy roads, they will cause severe wear to the road surface and are not suitable for use on urban roads.

[0005] Therefore, in order to effectively solve the above problems, the present application provides a low-temperature resistant and highly anti-skid automobile tire and a preparation method thereof. The rubber material prepared in the present application and the automobile tire prepared therefrom can ensure excellent low-temperature resistance and anti-skid performance while maintaining excellent waterproof, aging resistance and mechanical stability in a low-temperature environment, and has a very excellent market prospect. Summary of the invention

[0006] In order to solve the above problems, the first aspect of the present application provides a low-temperature resistant and highly anti-skid automobile tire. The raw materials are, by mass: 40 to 50 parts of natural rubber, 20 to 40 parts of mixed rubber, 10 to 15 parts of plasticizer, 1 to 2.5 parts of antioxidant, 1 to 2 parts of vulcanizer, 1 to 2 parts of accelerator, 2 to 3 parts of dispersant, 3 to 8 parts of anti-skid agent, 2 to 3 parts of activator, 30 to 50 parts of modified filler, and 20 to 30 parts of modified resin.

[0007] As a preferred solution, the mass ratio of the natural rubber, the mixed rubber, the modified filler and the modified resin is (42-48): (25-35): (35-45): (22-25).

[0008] As a preferred solution, the mass ratio of the natural rubber, the mixed rubber, the modified filler and the modified resin is (44-46): (28-32): (36-42): (24-25).

[0009] As a preferred solution, the Mooney viscosity of the natural rubber is 60-80, and the condition is: ML1+4@100°C.

[0010] As a preferred solution, the Mooney viscosity of the natural rubber is 65-70, and the condition is ML1+4@100°C.

[0011] As a preferred solution, the mixed rubber is a composition of EPDM rubber and styrene-butadiene rubber.

[0012] As a preferred solution, the mass ratio of the EPDM rubber to the styrene-butadiene rubber is (3-4):(1-1.5).

[0013] As a preferred solution, the mass ratio of the EPDM rubber to the styrene-butadiene rubber is (3.6-3.8):(1-1.2).

[0014] As a preferred solution, the plasticizer is at least one of cyclohexane oil, white oil, paraffin oil and polyester resin.

[0015] As a preferred solution, the plasticizer is cyclohexane oil.

[0016] As a preferred solution, the antioxidant is at least one of 6PPD, MB, IPPD, DPPD, BHT and AO-2246.

[0017] As a preferred solution, the antioxidant is 6PPD.

[0018] As a preferred solution, the vulcanizing agent is sulfur.

[0019] As a preferred solution, the accelerator is at least one of CZ, CBS, DOTG, ZDEC, MBT, and MBTS.

[0020] As a preferred solution, the accelerator is CBS.

[0021] As a preferred solution, the dispersant is at least one of stearic acid, sodium stearate, zinc stearate, sodium lauryl sulfate, PEG, hexadecyltrimethylammonium bromide and PVP.

[0022] As a preferred solution, the dispersant is a combination of stearic acid and PVP.

[0023] As a preferred solution, the mass ratio of stearic acid to PVP is (2-3): (0.8-1.2).

[0024] As a preferred solution, the anti-slip agent is ceramic microbeads.

[0025] As a preferred solution, the average particle size of the ceramic microbeads is 20 to 25 μm.

[0026] As a preferred solution, the activator is zinc oxide.

[0027] As a preferred solution, the average particle size of the zinc oxide is 20 to 35 nm.

[0028] As a preferred solution, the preparation method of the modified filler specifically includes the following steps: S1: adding chopped carbon fiber, tetraethyl orthosilicate, glutaric anhydride and γ-aminopropyltriethoxysilane to DMF, heating to 70-80°C and keeping warm for 4-5 hours, centrifuging, washing and drying after the reaction is completed to obtain a pre-treated mixture; S2: mixing the pre-treated mixture, ammonia water and triethylamine and adding them to deionized water, heating to 60-80°C, keeping warm for 3-3.5 hours, and centrifuging after the reaction is completed. Filter and dry to obtain pretreated particles; S3: mix the pretreated particles and copper acetate, add them to the DMF solution and stir evenly, then heat it to 80-90°C and add the DMF solution containing trimesic acid dropwise for 2-2.5 hours. After the addition is completed, heat it to 120-140°C, stir at 100-120r / min to react for 10-12 hours, add triethanolamine and mix and stir for 5-10 minutes after the reaction is completed, cool to room temperature naturally and precipitate, centrifuge and filter to obtain the precipitate, and dry it.

[0029] As a preferred solution, the mass ratio of the chopped carbon fibers, tetraethyl orthosilicate, glutaric anhydride and γ-aminopropyltriethoxysilane is (4-5): (0.5-0.8): (1-1.2): (0.2-0.3).

[0030] As a preferred solution, the mass ratio of the pretreatment mixture, ammonia water and triethylamine is (3-3.5): (0.8-1): (0.2-0.25).

[0031] As a preferred solution, the mass ratio of the pretreated particles, copper acetate, trimesic acid and triethanolamine is (2-2.5): (1.8-2.2): (1.1-1.3): (0.1-0.2).

[0032] As a preferred solution, the average diameter of the chopped carbon fibers is 4 to 5 μm, and the average length is 4 to 6 mm.

[0033] In the present application, the addition of the modified filler can effectively improve the low temperature and anti-skid performance of the automobile outer tire while maintaining excellent waterproof, mechanical stability and aging resistance. The added modified filler can take the short chopped carbon fiber as the linear center, and symmetrically form a composite surface structure with skeleton particles as the main body and amorphous silica covered on the fiber surface. The existence of this structure can provide an excellent anti-skid site for the rubber system of the automobile outer tire through its continuous groove structure, and through the existence of the groove site, it can attract and guide the surface moisture to move to the skeleton particles, and finally adsorb and remove the surface moisture through the adsorption effect of the skeleton pores, and can stably keep the moisture from desorption at low temperatures, thereby achieving excellent anti-skid, waterproof and low temperature resistance at low temperatures; and on the other hand, the modified filler can take the short chopped carbon fiber as the main body structure to form a connector with excellent connection and adhesion effect, so that the carbon fiber can be used as a support and connection carrier for the internal stress inside the rubber material, and the good connection effect of the surface composite particles on the rubber system can greatly improve the mechanical properties and mechanical stability.

[0034] As a preferred solution, the preparation method of the modified resin specifically includes the following steps: S1: adding hydroxyethyl acrylate, phenyl acrylate and benzophenone into a reaction container under nitrogen at a wavelength of 360-390nm for irradiation reaction for 2-2.5h, and filtering the precipitation after the reaction to obtain a prepolymer monomer; S2: adding the prepolymer monomer, acrylamide and glycidyl methacrylate into an acetone solution, heating to 85-90°C, stirring at a speed of 80-100r / min to keep the temperature for reaction for 4-5h, then cooling to 60-70°C, adding starch, and continuing to stir and react for 1.5-2.5h. After completion, adding triethylamine to the product solution to adjust the pH to 7.5-8, then naturally precipitating and filtering, vacuum drying to a moisture content of ≤2.5wt%, taking out and sealing.

[0035] As a preferred solution, the mass ratio of hydroxyethyl acrylate, phenyl acrylate and benzophenone is (8-10):(2-3):(0.2-0.25).

[0036] As a preferred solution, the mass ratio of the prepolymer monomer, acrylamide, methacrylic acid hydrate and amylopectin is (10-15): (35-45): (3-5): (1.5-2.5).

[0037] As a preferred solution, the starch is amylopectin; the amylopectin has a branch chain content of 70-80%.

[0038] The modified resin added in this application can help improve the anti-skid, low temperature resistance, waterproof and aging resistance of automobile outer tires. The added modified resin can serve as a good transport carrier for the added modified filler in the rubber system, thereby serving as a medium for the modified particles to achieve internal strong connection in the rubber system; on the other hand, the added modified resin can participate in the internal cross-linking of the rubber system, and through the multi-branched construction of amylopectin, the degree of molecular chain entanglement of the internal system is greatly increased, the density of the molecular chain network is improved, the penetration speed of water molecules is effectively reduced, the penetration resistance is improved, and a micro-resin surface can also be formed on the surface of the rubber material, promoting the dispersion effect of anti-skid micro-beads on the surface, thereby effectively improving the various performances of automobile outer tires.

[0039] The second aspect of the present application provides a method for preparing the above-mentioned low-temperature resistant and highly anti-skid automobile outer tire, which specifically includes the following steps: S1: putting natural rubber and mixed rubber into an internal mixer, mixing and preheating at 100-110°C for 5-10 minutes, then adding modified filler, modified resin, plasticizer and dispersant and mixing for 5-8 minutes, and continuing to add antioxidant and anti-skid agent and mixing for 6-9 minutes; S2: adding vulcanizer, accelerator and activator and mixing for 6-8 minutes, after ensuring that all components are evenly dispersed, taking out the mixed rubber material, cooling it to room temperature, and using an extruder to extrude the cooled rubber material into the desired tread shape and placing the extruded tread in a tire mold for molding; S3: placing the molded tire into a vulcanizing tank, setting the vulcanization temperature to 140-165°C, the vulcanization pressure to 1.5-2MPa, and the vulcanization time to 30-40 minutes. After the vulcanization is completed, take out the tire, cool it naturally to room temperature, and obtain it after the inspection is completed.

[0040] The beneficial effects of this application are:

[0041] 1. The present application provides a low-temperature resistant and highly anti-skid automobile tire, which can ensure excellent low-temperature resistance and anti-skid performance while maintaining excellent waterproof, aging resistance and mechanical stability in a low-temperature environment, and has a very excellent market prospect.

[0042] 2. A low-temperature resistant and highly anti-skid automobile tire provided in the present application can, by adding modified fillers, symmetrically form a composite surface structure with skeleton particles as the main body and amorphous silica covered on the fiber surface with short chopped carbon fibers as the linear center. The existence of this structure can provide excellent anti-skid sites for the rubber system of the automobile tire through its continuous groove structure, and the presence of the groove sites can attract and guide surface moisture to move toward the skeleton particles, and finally remove surface moisture through the adsorption effect of the skeleton pores, and can stably maintain moisture without desorption at low temperatures, thereby achieving excellent anti-skid, waterproof and low-temperature resistant performance at low temperatures.

[0043] 3. A low-temperature resistant and highly anti-skid automobile tire provided in the present application can form a connector with excellent connection and adhesion effects with chopped carbon fibers as the main line structure by adding modified fillers, so that the carbon fibers can be used as a support and connection carrier for internal stress inside the rubber material, and the good connection effect of the surface composite particles on the rubber system can greatly improve the mechanical properties and mechanical stability.

[0044] 4. A low-temperature resistant and highly anti-skid automobile tire provided in the present application can serve as a good transport carrier for the added modified filler in the rubber system by adding a modified resin, thereby serving as a medium for the modified particles in the rubber system to achieve strong internal connection. On the other hand, the added modified resin can participate in the internal cross-linking of the rubber system, and through the multi-branch building effect of branched starch, the degree of entanglement of the molecular chains in the internal system is greatly increased, the density of the molecular chain network is improved, the penetration rate of water molecules is effectively reduced, and the penetration resistance is increased. A micro-resin surface can also be formed on the surface of the rubber material, which promotes the dispersion effect of the anti-skid microbeads on the surface, thereby effectively improving the various performances of the automobile tire. DETAILED DESCRIPTION

[0045] The following will further explain and demonstrate the technical solutions in the above invention content of this application in the form of specific implementation schemes. The following embodiments are only practical examples used to illustrate and explain the contents of the technical solutions in the specification, and should not limit the scope of the claims to be protected by this application. All technical products based on the technical solutions described in the invention content of this application should be included in the scope to be protected by this application.

[0046] In the following examples, unless otherwise specified, the raw materials are all commercially available products, or can be prepared by methods well known to those skilled in the art.

[0047] Example 1

[0048] Example 1 The first aspect provides a low-temperature resistant and highly anti-skid automobile tire. The raw materials are, by mass: 45.5 parts of natural rubber, 30 parts of mixed rubber, 12.5 parts of plasticizer, 1.2 parts of antioxidant, 1.6 parts of vulcanizer, 1.2 parts of accelerator, 2.8 parts of dispersant, 5.6 parts of anti-skid agent, 2.1 parts of activator, 38 parts of modified filler, and 24.4 parts of modified resin.

[0049] The Mooney viscosity of the natural rubber was 68, under the condition of ML1+4@100°C, and the product of model TSR 20 was purchased from the Thai Natural Rubber Public Company.

[0050] The mixed rubber is a composition of EPDM rubber and styrene butadiene rubber, with a mass ratio of 3.8: 1. The EPDM rubber was purchased from the 3112M model sold by Sinopec; the styrene butadiene rubber was purchased from the F875 model sold by Dongguan Xinrun Trading Co., Ltd.

[0051] The plasticizer is cyclohexane oil, which is a 4016 type high-viscosity cyclohexane oil product purchased from Hebei Yunjin Lubricant Company; the antioxidant is 6PPD; the vulcanizing agent is sulfur; and the accelerator is CBS.

[0052] The dispersant is a composition of stearic acid and PVP-K60, and the mass ratio of the two is 2.5:1.

[0053] The anti-slip agent is ceramic microbeads with an average particle size of 22.5 μm, which are purchased from Shanghai Gerunya Materials Co., Ltd.

[0054] The activator is zinc oxide with an average particle size of 24 nm.

[0055] The preparation method of the modified filler specifically comprises the following steps: S1: 4.6 parts of chopped carbon fibers, 0.7 parts of tetraethyl orthosilicate, 1.1 parts of glutaric anhydride and 0.22 parts of γ-aminopropyltriethoxysilane are mixed and added to 120 parts of DMF, the temperature is raised to 78°C and the reaction is kept warm for 4.5 hours, and after the reaction is completed, the pre-treated mixture is centrifuged, washed and dried to obtain a pre-treated mixture; S2: 3.4 parts of the pre-treated mixture, 0.85 parts of ammonia water and 0.21 parts of triethylamine are mixed and added to 80 parts of deionized water, the temperature is raised to 65°C, and the reaction is kept warm for 3 hours. h, after the reaction is completed, centrifuge and filter and dry to obtain pretreated particles; S3: 2.4 parts of pretreated particles and 2.1 parts of copper acetate are mixed and added to 80 parts of DMF solution and stirred evenly, then the temperature is raised to 85°C and 40 parts of DMF solution containing 1.2 parts of trimesic acid are added dropwise for 2 hours. After the addition is completed, the temperature is raised to 125°C and stirred at 120r / min for 11 hours. After the reaction is completed, triethanolamine is added and mixed and stirred for 8 minutes, and the mixture is naturally cooled to room temperature and precipitated. The precipitate is centrifuged and filtered to obtain the obtained product after drying.

[0056] The chopped carbon fibers had an average diameter of 4.5 μm and an average length of 6 mm, and were purchased from Shanghai Lishuo Composite Materials Co., Ltd.

[0057] The preparation method of the modified resin specifically comprises the following steps: S1: adding 10 parts of hydroxyethyl acrylate, 2.5 parts of phenyl acrylate and 0.23 parts of benzophenone into a reaction container under nitrogen at a wavelength of 385nm for reaction for 2.2 hours, and filtering the precipitation after the reaction is completed to obtain a prepolymer monomer; S2: adding 12.6 parts of the prepolymer monomer, 40.5 parts of acrylamide and 4.5 parts of glycidyl methacrylate into 350 parts of acetone solution, heating to 85°C, stirring at a speed of 100r / min for heat preservation for reaction for 4.5 hours, then cooling to 65°C, adding starch, continuing to stir and react for 2 hours, and after completion, adding triethylamine into the product solution to adjust the pH to 7.6, then naturally precipitating and filtering, vacuum drying to a moisture content of ≤2.5wt%, taking out and sealing to obtain the product.

[0058] The starch is amylopectin with a branched chain content of 75%, and is purchased from a product with a corresponding content sold by Wuhan Lanabai Company.

[0059] The second aspect of the present embodiment provides a method for preparing the above-mentioned low-temperature resistant and highly anti-skid automobile outer tire, which specifically includes the following steps: S1: putting natural rubber and mixed rubber into an internal mixer, mixing and preheating at 110°C for 6 minutes, then adding modified filler, modified resin, plasticizer and dispersant and mixing for 7 minutes, and continuing to add antioxidant and anti-skid agent and mixing for 8 minutes; S2: adding vulcanizer, accelerator and activator and mixing for 6 minutes, after ensuring that all components are evenly dispersed, taking out the mixed rubber material, cooling it to room temperature, and using an extruder to extrude the cooled rubber material into the desired tread shape and placing the extruded tread in a tire mold for molding; S3: placing the molded tire into a vulcanizing tank, setting the vulcanization temperature to 145°C, the vulcanization pressure to 2MPa, and the vulcanization time to 33 minutes. After the vulcanization is completed, take out the tire, cool it naturally to room temperature, and obtain it after the inspection is completed.

[0060] Example 2

[0061] Example 2 The first aspect provides a low-temperature resistant and highly anti-skid automobile tire. The raw materials, in parts by mass, are: 48 parts of natural rubber, 25.5 parts of mixed rubber, 13.2 parts of plasticizer, 1.4 parts of antioxidant, 1.8 parts of vulcanizer, 1.1 parts of promoter, 2.2 parts of dispersant, 5.2 parts of anti-skid agent, 2.2 parts of activator, 35.5 parts of modified filler, and 22.3 parts of modified resin.

[0062] The Mooney viscosity of the natural rubber was 68, under the condition of ML1+4@100°C, and the product of model TSR 20 was purchased from the Thai Natural Rubber Public Company.

[0063] The mixed rubber is a composition of EPDM rubber and styrene butadiene rubber, with a mass ratio of 3.6:1.2. The EPDM rubber was purchased from the 3112M model sold by Sinopec; the styrene butadiene rubber was purchased from the F875 model sold by Dongguan Xinrun Trading Co., Ltd.

[0064] The plasticizer is cyclohexane oil, which is a 4016 type high-viscosity cyclohexane oil product purchased from Hebei Yunjin Lubricant Company; the antioxidant is 6PPD; the vulcanizing agent is sulfur; and the accelerator is CBS.

[0065] The dispersant is a composition of stearic acid and PVP-K60, and the mass ratio of the two is 3:1.

[0066] The anti-slip agent is ceramic microbeads with an average particle size of 22.5 μm, which are purchased from Shanghai Gerunya Materials Co., Ltd.

[0067] The activator is zinc oxide with an average particle size of 24 nm.

[0068] The preparation method of the modified filler specifically comprises the following steps: S1: 4.6 parts of chopped carbon fibers, 0.7 parts of tetraethyl orthosilicate, 1.1 parts of glutaric anhydride and 0.22 parts of γ-aminopropyltriethoxysilane are mixed and added to 120 parts of DMF, the temperature is raised to 78°C and the reaction is kept warm for 4.5 hours, and after the reaction is completed, the pre-treated mixture is centrifuged, washed and dried to obtain a pre-treated mixture; S2: 3.4 parts of the pre-treated mixture, 0.85 parts of ammonia water and 0.21 parts of triethylamine are mixed and added to 80 parts of deionized water, the temperature is raised to 65°C, and the reaction is kept warm for 3 hours. h, after the reaction is completed, centrifuge and filter and dry to obtain pretreated particles; S3: 2.4 parts of pretreated particles and 2.1 parts of copper acetate are mixed and added to 80 parts of DMF solution and stirred evenly, then the temperature is raised to 85°C and 40 parts of DMF solution containing 1.2 parts of trimesic acid are added dropwise for 2 hours. After the addition is completed, the temperature is raised to 125°C and stirred at 120r / min for 11 hours. After the reaction is completed, triethanolamine is added and mixed and stirred for 8 minutes, and the mixture is naturally cooled to room temperature and precipitated. The precipitate is centrifuged and filtered to obtain the obtained product after drying.

[0069] The chopped carbon fibers had an average diameter of 4.5 μm and an average length of 6 mm, and were purchased from Shanghai Lishuo Composite Materials Co., Ltd.

[0070] The preparation method of the modified resin specifically comprises the following steps: S1: adding 10 parts of hydroxyethyl acrylate, 2.5 parts of phenyl acrylate and 0.23 parts of benzophenone into a reaction container under nitrogen at a wavelength of 385nm for reaction for 2.2 hours, and filtering the precipitation after the reaction is completed to obtain a prepolymer monomer; S2: adding 12.6 parts of the prepolymer monomer, 40.5 parts of acrylamide and 4.5 parts of glycidyl methacrylate into 350 parts of acetone solution, heating to 85°C, stirring at a speed of 100r / min for heat preservation for reaction for 4.5 hours, then cooling to 65°C, adding starch, continuing to stir and react for 2 hours, and after completion, adding triethylamine into the product solution to adjust the pH to 7.6, then naturally precipitating and filtering, vacuum drying to a moisture content of ≤2.5wt%, taking out and sealing to obtain the product.

[0071] The starch is amylopectin with a branched chain content of 75%, and is purchased from a product with a corresponding content sold by Wuhan Lanabai Company.

[0072] The second aspect of the present embodiment provides a method for preparing the above-mentioned low-temperature resistant and highly anti-skid automobile outer tire, which specifically includes the following steps: S1: putting natural rubber and mixed rubber into an internal mixer, mixing and preheating at 110°C for 6 minutes, then adding modified filler, modified resin, plasticizer and dispersant and mixing for 7 minutes, and continuing to add antioxidant and anti-skid agent and mixing for 8 minutes; S2: adding vulcanizer, accelerator and activator and mixing for 6 minutes, after ensuring that all components are evenly dispersed, taking out the mixed rubber material, cooling it to room temperature, and using an extruder to extrude the cooled rubber material into the desired tread shape and placing the extruded tread in a tire mold for molding; S3: placing the molded tire into a vulcanizing tank, setting the vulcanization temperature to 145°C, the vulcanization pressure to 2MPa, and the vulcanization time to 33 minutes. After the vulcanization is completed, take out the tire, cool it naturally to room temperature, and obtain it after the inspection is completed.

[0073] Comparative Example 1

[0074] The specific implementation method of this comparative example is basically the same as that of Example 1, except that: the low-temperature resistant and highly anti-skid automobile outer tire, in parts by mass, the raw materials are: 55 parts of natural rubber, 18 parts of mixed rubber, 12.5 parts of plasticizer, 1.2 parts of antioxidant, 1.6 parts of vulcanizing agent, 1.2 parts of accelerator, 2.8 parts of dispersant, 5.6 parts of anti-skid agent, 2.1 parts of activator, 25 parts of modified filler, and 33 parts of modified resin.

[0075] Comparative Example 2

[0076] The specific implementation method of this comparative example is basically the same as that of Example 1, except that: the low-temperature resistant and highly anti-skid automobile outer tire, in parts by mass, comprises the following raw materials: 40.5 parts of natural rubber, 42 parts of mixed rubber, 6.5 parts of plasticizer, 1.2 parts of antioxidant, 1.6 parts of vulcanizing agent, 1.2 parts of accelerator, 2.1 parts of dispersant, 5.6 parts of anti-skid agent, 2.1 parts of activator, 48.8 parts of modified filler and 12.5 parts of modified resin.

[0077] Comparative Example 3

[0078] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified filler specifically includes the following steps: S1: 2.2 parts of chopped carbon fibers, 1 part of tetraethyl orthosilicate, 0.6 parts of glutaric anhydride and 0.11 parts of γ-aminopropyltriethoxysilane are mixed and added to 100 parts of DMF, and the temperature is raised to 78°C and kept for reaction for 4.5 hours. After the reaction is completed, centrifugation, washing and drying are performed to obtain a pretreated mixture; S2: 3.4 parts of the pretreated mixture, 0.85 parts of ammonia water and 0.21 parts of triethylamine are mixed and added to 80 parts of deionized water , heat to 65℃, keep warm for reaction for 3h, centrifuge and dry after the reaction is completed to obtain pretreated particles; S3: mix 2.4 parts of pretreated particles and 2.1 parts of copper acetate, add to 80 parts of DMF solution and stir evenly, then heat to 85℃ and add 40 parts of DMF solution containing 1.2 parts of trimesic acid, the addition time is 2h, after the addition is completed, heat to 125℃, stir at 120r / min for reaction for 11h, after the reaction is completed, add triethanolamine and mix and stir for 8min, naturally cool to room temperature and precipitate, centrifuge to obtain the precipitate, and dry to obtain.

[0079] Comparative Example 4

[0080] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified filler specifically includes the following steps: S1: 4.6 parts of chopped carbon fibers, 0.7 parts of tetraethyl orthosilicate, 1.1 parts of glutaric anhydride and 0.22 parts of γ-aminopropyltriethoxysilane are mixed and added to 120 parts of DMF, and the temperature is raised to 78°C and kept for reaction for 4.5 hours. After the reaction is completed, centrifuge, wash and dry to obtain a pretreated mixture; S2: 3.4 parts of the pretreated mixture, 0.85 parts of ammonia water and 0.21 parts of triethylamine are mixed and added to 80 parts of deionized water S3: 4.8 parts of pretreated particles and 1.2 parts of copper acetate were mixed and added to 80 parts of DMF solution and stirred evenly. Then the temperature was raised to 85°C and 20 parts of DMF solution containing 0.5 parts of trimesic acid were added dropwise for 2 hours. After the addition was completed, the temperature was raised to 125°C and stirred at 120r / min for 11 hours. After the reaction was completed, triethanolamine was added and mixed and stirred for 8 minutes. The mixture was naturally cooled to room temperature and precipitated. The precipitate was filtered by centrifugation and dried to obtain the obtained particles.

[0081] Comparative Example 5

[0082] The specific implementation of this comparative example is basically the same as that of Example 1, except that the average diameter of the chopped carbon fibers is 8.5 μm, the average length is 12 mm, and the corresponding size products are purchased from Shanghai Lishuo Composite Materials Co., Ltd.

[0083] Comparative Example 6

[0084] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified resin specifically comprises the following steps: S1: adding 5 parts of hydroxyethyl acrylate, 4.5 parts of phenyl acrylate and 0.12 parts of benzophenone into a reaction container and irradiating the reaction under nitrogen at a wavelength of 385 nm for 2.2 hours. After the reaction, the precipitate is filtered to obtain a prepolymer monomer; S2: adding 12.6 parts of the prepolymer monomer, 40.5 parts of acrylamide and 4.5 parts of glycidyl methacrylate into 350 parts of acetone solution, heating the solution to 85°C, stirring at a speed of 100 r / min to keep the temperature for 4.5 hours, then cooling the solution to 65°C and adding starch, continuing to stir and react for 2 hours, after completion, adding triethylamine into the product solution to adjust the pH to 7.6, then naturally precipitating and filtering, vacuum drying to a moisture content of ≤2.5wt%, taking out and sealing.

[0085] Comparative Example 7

[0086] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified resin specifically comprises the following steps: S1: adding 10 parts of hydroxyethyl acrylate, 2.5 parts of phenyl acrylate and 0.23 parts of benzophenone into a reaction container and irradiating the reaction under nitrogen at a wavelength of 385 nm for 2.2 hours. After the reaction, the precipitate is filtered to obtain a prepolymer monomer; S2: adding 8.5 parts of the prepolymer monomer, 45.5 parts of acrylamide and 6.5 parts of glycidyl methacrylate into 380 parts of acetone solution, heating the solution to 85°C, stirring at a speed of 100 r / min to keep the temperature for 4.5 hours, then cooling the solution to 65°C and adding starch, continuing to stir and react for 2 hours, after completion, adding triethylamine into the product solution to adjust the pH to 7.6, then naturally precipitating and filtering, vacuum drying to a moisture content of ≤2.5wt%, taking out and sealing.

[0087] Performance Evaluation

[0088] 1. Low temperature resistance test: The low temperature shrinkage rate test was carried out on the automobile tires prepared in the embodiment and the comparative example with reference to the standard GB / T 7758-2020. The test starting temperature was 23±2°C, the cooling rate was 1.5°C / min, and the test value was the average value of 10 tests and recorded in Table 1.

[0089] 2. Anti-skid test: The test was conducted on an actual ice and snow road in Harbin in January to ensure that the road was covered with an even layer of snow. Vehicle status: The vehicle was in good condition, with the brake system, suspension system, etc. working properly, and the tires to be tested were installed. Vehicle weight: 1200kg. Initial speed: 40km / h. Test method: A speed sensor was used to ensure that the vehicle reached an accurate speed before the test. The vehicle accelerated from a stationary state to the specified initial speed. The driver immediately stepped on the brakes at the specified speed until the vehicle came to a complete stop. A laser rangefinder or other high-precision measuring tool was used to record the distance from the start of braking to the complete stop of the vehicle. After 5 tests, the braking distance of each test was recorded and the average value was calculated. The results were recorded in Table 2.

[0090] 3. Waterproof test: 2cm×2cm×0.5cm samples of the automobile outer tires prepared in the embodiments and comparative examples were taken for moisture permeability test. The test was conducted in accordance with the reference standard GB / T 1037-1988. The test temperature was 25±2°C and the test humidity was 50±5%RH. The test values ​​were the average of 10 tests and recorded in Table 2.

[0091] 4. Aging resistance test: Take 2cm×2cm×0.5cm samples of the automobile outer tires prepared in the embodiments and comparative examples, test their tensile strength (MPa), then store the samples in a constant temperature and humidity environment of 65±2℃, 80% relative humidity for 3 months, take them out after 3 months, test their tensile strength (MPa) again, calculate and record the tensile strength retention rate (%) after the test, tensile strength retention rate (%) = tensile strength after test / tensile strength before test × 100%, and take the average value of 10 sample tests and record it in Table 2.

[0092] Table 1 Performance test results 1

[0093]

[0094]

[0095] Table 1 Performance test results 2

[0096]

[0097] It can be seen from the data results of the embodiments and comparative examples of the present application and Table 1 and Table 2 that embodiments 1 and 2 of the present application have obvious advantages over comparative examples 1 to 7 in terms of low temperature resistance, anti-skid performance, waterproof performance and aging resistance of automobile outer tires. This is mainly due to the combined effect of the modified resin and modified fiber material added as specified in the present application. Comparative examples 1 to 7 did not adopt the technical solution specified in the present application, resulting in obvious disadvantages in the above performance tests. This further proves the necessity of the technical solution specified in the present application for the technical effect of the present application and solving technical problems.

Claims

1. A low temperature resistant and highly anti-skid automobile tire, characterized by: Low temperature resistant and highly anti-skid automobile outer tire, the raw materials are, by weight: 40-50 parts of natural rubber, 20-40 parts of mixed rubber, 10-15 parts of plasticizer, 1-2.5 parts of antioxidant, 1-2 parts of vulcanizer, 1-2 parts of accelerator, 2-3 parts of dispersant, 3-8 parts of anti-skid agent, 2-3 parts of activator, 30-50 parts of modified filler, 20-30 parts of modified resin; The Mooney viscosity of the natural rubber is 60-80, condition: ML1+4@100°C; The mixed rubber is a composition of EPDM rubber and styrene-butadiene rubber; the mass ratio of the EPDM rubber to the styrene-butadiene rubber is (3-4): (1-1.5); The plasticizer is at least one of naphthenic oil, white oil, paraffin oil and polyester resin; The antioxidant is at least one of 6PPD, MB, IPPD, DPPD, BHT and AO-2246; The preparation method of the modified filler specifically comprises the following steps: S1: adding chopped carbon fiber, tetraethyl orthosilicate, glutaric anhydride and γ-aminopropyltriethoxysilane to DMF, heating to 70-80°C and keeping warm for 4-5 hours, centrifuging, washing and drying after the reaction is completed to obtain a pre-treated mixture; S2: adding the pre-treated mixture, ammonia water and triethylamine to deionized water, heating to 60-80°C, keeping warm for 3-3.5 hours, centrifuging, filtering and drying after the reaction is completed to obtain a pre-treated mixture. to pretreated particles; S3: the pretreated particles and copper acetate are mixed and added to the DMF solution and stirred evenly, then the temperature is raised to 80-90°C and the DMF solution containing trimesic acid is added dropwise for 2-2.5 hours, and after the addition is completed, the temperature is raised to 120-140°C, and the reaction is stirred at a speed of 100-120 r / min for 10-12 hours, and after the reaction is completed, triethanolamine is added and mixed and stirred for 5-10 minutes, and the mixture is naturally cooled to room temperature and precipitated, and the precipitate is obtained by centrifugation and filtration, and then dried; The mass ratio of the chopped carbon fiber, tetraethyl orthosilicate, glutaric anhydride and gamma-aminopropyltriethoxysilane is (4-5): (0.5-0.8): (1-1.2): (0.2-0.3).

2. The low temperature resistant and highly anti-skid automobile tire according to claim 1, characterized in that: The mass ratio of the natural rubber, the mixed rubber, the modified filler and the modified resin is (42-48): (25-35): (35-45): (22-25).

3. The low temperature resistant and highly anti-skid automobile tire according to claim 2, characterized in that: The dispersant is at least one of stearic acid, sodium stearate, zinc stearate, sodium lauryl sulfate, PEG, hexadecyltrimethylammonium bromide and PVP.

4. The low temperature resistant and highly anti-skid automobile tire according to claim 3, characterized in that: The anti-slip agent is ceramic micro beads; the average particle size of the ceramic micro beads is 20 to 25 μm.

5. The low temperature resistant and highly anti-skid automobile tire according to claim 4, characterized in that: The activator is zinc oxide; the average particle size of the zinc oxide is 20-35 nm.

6. The low temperature resistant and highly anti-skid automobile tire according to claim 5, characterized in that: The mass ratio of the pretreatment mixture, ammonia water and triethylamine is (3-3.5): (0.8-1): (0.2-0.25); the mass ratio of the pretreatment particles, copper acetate, trimesic acid and triethanolamine is (2-2.5): (1.8-2.2): (1.1-1.3): (0.1-0.2).

7. The low temperature resistant and highly anti-skid automobile tire according to claim 6, characterized in that: The average diameter of the chopped carbon fibers is 4 to 5 μm, and the average length is 4 to 6 mm.

8. The low temperature resistant and highly anti-skid automobile tire according to claim 7, characterized in that: The preparation method of the modified resin specifically comprises the following steps: S1: adding hydroxyethyl acrylate, phenyl acrylate and benzophenone into a reaction container under nitrogen with a wavelength of 360-390nm for irradiation reaction for 2-2.5h, and filtering the precipitation after the reaction to obtain a prepolymer monomer; S2: adding the prepolymer monomer, acrylamide and glycidyl methacrylate into an acetone solution, heating the solution to 85-90°C, stirring at a speed of 80-100r / min for heat preservation reaction for 4-5h, then cooling the solution to 60-70°C, adding starch, and continuing to stir and react for 1.5-2.5h. After completion, adding triethylamine into the product solution to adjust the pH to 7.5-8, then filtering the precipitation naturally, and vacuum drying the solution to a moisture content of ≤2.5wt%, and then taking out and sealing the solution.

9. The low temperature resistant and highly anti-skid automobile tire according to claim 8, characterized in that: The mass ratio of hydroxyethyl acrylate, phenyl acrylate and benzophenone is (8-10): (2-3): (0.2-0.25); the mass ratio of the prepolymer monomer, acrylamide, methacrylic acid condensate and amylopectin is (10-15): (35-45): (3-5): (1.5-2.5); the starch is amylopectin; the branch content of the amylopectin is 70-80%.

10. A method for preparing a low temperature resistant and highly skid resistant automobile outer tire according to any one of claims 1 to 9, characterized in that: The specific steps include: S1: Put the natural rubber and mixed rubber into an internal mixer, preheat at 100-110℃ for 5-10min, then add the modified filler, modified resin, plasticizer and dispersant and mix for 5-8min, continue to add the antioxidant and anti-skid agent and mix for 6-9min; S2: Add the vulcanizer, accelerator and activator and mix for 6-8min. After ensuring that all the ingredients are evenly dispersed, take out the mixed rubber and cool it to room temperature. The extruder extrude the cooled rubber into the required tread shape and place the extruded tread in the tire mold for molding; S3: Put the molded tire into a vulcanizing tank, set the vulcanization temperature to 140-165℃, the vulcanization pressure to 1.5-2MPa, and the vulcanization time to 30-40min. After the vulcanization is completed, take out the tire and cool it naturally to room temperature. After the inspection is completed, it is ready.